Application of Media Big Book to Develop the Ability to Read the Beginning in Madrasah Ibtidaiyah - Zainudin, Agus; Febriyanti, Beby Dwi; Zubaidah, Siti (EDUCARE: Journal of Primary Education, 2023)
This study aims to explore the use of big book media in supporting grade 1 students at MI Al Marhamah Jember in developing their early reading skills. A big book is characterized by its large size, featuring bigger text and illustrations compared to standard books, which helps attract students' attention. This research employs a qualitative approach with a descriptive methodology, involving teachers and students as participants. The focus of the study is on the implementation of big book media to enhance the beginning reading abilities of first-grade students. Data was collected through observations, interviews, and documentation, while data analysis involved processes of data reduction, data presentation, and conclusion drawing. The findings indicate that the use of big book media effectively aids students in acquiring initial reading skills at MI Al Marhamah Jember. This is demonstrated by the students' ability to read text from the big books, pronounce syllables, spell out words, and connect syllables to form simple words. Moreover, many students showed progress in reading simple sentences fluently.